The mediating role of work motivation: The effect of leadership, workload, and reward on employee performance - Gilang Rahmadhon; Vera Firdaus; Sumartik Sumartik (Universitas Ahmad Dahlan, 2024)
Employee performance is considered key in achieving company goals, reflecting commitment, dedication and contribution to the company's vision. Motivation, as the main driver in the work environment, is a key factor in motivating employees to contribute optimally. Effective leaders have the ability to influence employee behavior. Heavy workloads, especially for drivers and helpers, can have a negative impact on employee motivation. Companies are advised to seek an optimal balance in workload to ensure employee well-being and productivity. Recognition and reward strategies are expected to maintain high quality employees. The aim of this research is to analyze the relationship and influence of leadership, workload and rewards on employee performance with work motivation as a mediating variable at liquefied petroleum gas distributors in Sidoarjo, Indonesia. This research used a cluster sampling technique with a total of 105 respondents. SPSS software was used to analyze the data. The findings demonstrate leadership, workload and rewards have a positive effect on employee performance, however work motivation cannot mediate leadership, workload and rewards on employee performance.